Intraoperative Computed Tomography Angiography: A Novel Completion Imaging Modality for Carotid Endarterectomy. Issue 6 (10th April 2017) - Sen, Anish N; Fridley, Jared; Sebastian, Sherly; Duckworth, Edward A M
Abstract: BACKGROUND: Intraoperative computed tomography angiography (ICTA) is a novel completion imaging modality for carotid endarterectomy (CEA). No studies exist in the literature describing ICTA use in CEA. OBJECTIVE: To evaluate the feasibility and efficacy of ICTA as a method of immediately evaluating the technical results of CEA. METHODS: Twenty-three consecutive CEAs were performed by a single neurosurgeon over an 8-month period. Of this series, 12 utilized ICTA for completion imaging, 10 utilized duplex ultrasonography (US), and 1 utilized no intraoperative completion imaging. Electronic medical records were reviewed to assess demographics, CTA results, US results, and need for revisions. RESULTS: Patients included 13 men (62%) and 8 women (38%). All patients had symptomatic internal carotid artery stenosis. Polytetrafluoroethylene (PTFE) patch angioplasty was used in 16 cases (70%). Average operative times were comparable between cases that utilized CTA and US, 180 and 175 min, respectively. Major technical defects were identified in one of the 12 cases utilizing ICTA and none of the 10 cases utilizing intraoperative US. The technical defect was revised without subsequent neurological complication. One patient had a postoperative intracerebral hemorrhage requiring surgical evacuation. Fifteen patients were followed for up to 3 months with no postoperative stroke or transient ischemic attacks. CONCLUSION: ICTA is a potentially safe and effective completion imaging modality compared to traditional alternatives, enabling the identification of technical deficits intraoperatively. While no statistically significant difference in operative times were noted between intraoperative CTA and US use, numerous steps must be taken to maximize the efficiency of ICTA.